×
Create a new article
Write your page title here:
We currently have 3,189 articles on s23. Type your article name above or create one of the articles listed here!



    s23
    3,189Articles
    in:
    Revision as of 15:39, 15 November 2006 by imported>Took (Automatic Proof)

    Axiome

    Kommutativ

    <math>A \land B = B \land A</math>

    <math>A \lor B = B \lor A</math>

    Assoziativ

    <math>(A \land B) \land C = A \land B \land C</math>

    <math>(A \lor B) \lor C = A \lor B \lor C</math>

    Distributiv

    <math>(A \land B) \lor (A \land C) = A \land (B \lor C)</math>

    <math>(A \lor B) \land (A \lor C) = A \lor (B \land C)</math>

    Vereinfachungsregeln

    <math>A \land 1 = A</math>

    <math>A \lor 1 = 1</math>


    <math>A \land 0 = 0</math>

    <math>A \lor 0 = A</math>


    <math>A \land A = A</math>

    <math>A \lor A = A</math>


    <math>\bar{A} \land A = 0</math>

    <math>\bar{A} \lor A = 1</math>


    <math>A \land (A \lor B) = A</math>

    <math>A \lor (A \land B = A</math>

    De Morgan Gesetze

    de-wp:De_Morgansche_Gesetze

    Examples

    1

    <math>Q = ( A \land B ) \lor ( A \land C )

       <=> A \land (B \lor C)</math>
    

    2

    <math>Q = ( C \lor B ) \land ( A \lor C )

       <=> C \lor (B \land A)</math>
    

    3

    <math>Y = ( A \land B) \lor ( C \land D) \lor ( D \land A ) \lor ( E \land C) <=>

     (A \land (B \lor D)) \lor ( C \land (D \lor E))</math>
    

    4

    <math>Z = ( A \land B ) \lor ( B \land A )

       <=> A \land B</math>
    

    5

    <math>Y = (\bar{C} \lor D \lor F) \land (\bar{C} \lor E \lor G)

       <=> \bar{C} \land ((D \land F) \land (G \lor E))</math>
    

    6

    <math>X = (( A \land B ) \lor C) \land (( A \lor B ) \lor D ))

     <=> (A \land B) \lor (C \land D)</math>
    
    ne das is nicht richtig so!
    betrachte A=0, B=1, C=1, D=0
    dann gilt: der linke ausdruck ist wahr, der rechte aber nicht.
    

    besser <math>X = (( A \land B ) \lor C) \land (( A \lor B ) \lor D ))

     <=> (A \land B) \lor ( C \land (A \lor B \lor D) )</math>
    

    7

    <math>X = ( C \lor D \lor F ) \land ( C \lor D \lor G )

     <=> C \lor D \lor (F \land G)</math>
    

    8

    <math>U = ( A \lor B ) \land ( A \land C )

       <=> ( A ) \land (A \land C) <=> A \land A \land C <=> A \land C</math>
    

    9

    <math>Q = (B \land C) \lor (B \land \bar{C})

       <=> B \land (C \lor \bar{C}) = B \land 1 = B</math>
    

    10

    <math>Y = ( G \lor \bar{F}) \land (G \lor F)

       <=> G \lor (F \land \bar{F}) = G \lor 0 = G</math>
    


    Are those right? I dont think so. Please check. --done :) --took 23:33, 14 November 2006 (CET) thank you, help is appreciated :) mutante 00:07, 15 November 2006 (CET)

    Automatic Proof

    with this little script u can check all of them by yourself. Just enter both conditions in line 9 and 11 and run it.

    #!/bin/bash
    for A in false true;
      do
      for B in false true
        do
        for C in false true;
          do
              x=0
              (($A && $B) || ($A && $C)) || x=1
              y=0
              ($A && ($B || $C)) || y=1
              if [ $x -eq $y ]
                then
                echo "ok"
                else
                echo "FALSCH - Belegung: A: $A, B: $B, C: $C"
                fi
          done
        done
      done
    
    Cookies help us deliver our services. By using our services, you agree to our use of cookies.
    Cookies help us deliver our services. By using our services, you agree to our use of cookies.